2024
DOI: 10.1021/acsapm.3c03082
|View full text |Cite
|
Sign up to set email alerts
|

Oligosiloxane-Based Epoxy Vitrimers: Adaptable Thermosetting Networks with Dual Dynamic Bonds

Amelia A. Putnam-Neeb,
Alex Stafford,
Sachin Babu
et al.

Abstract: Embedding dynamic covalent bonds into polymer compositions transforms static thermosets into active materials with the reprocessability of thermoplastics and the bulk properties of cross-linked networks. This class of next-generation materials, called covalent adaptable networks, shows significant promise in composites, soft optoelectronics, and robotics. Herein, we synthesized two oligosiloxane-based epoxy networks that provide fast dynamic bond exchange. Oligosiloxane diepoxides were cured with stoichiometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Indeed, the ultimate energy values obtained from CCSD­(T) calculations stand at 18.56 kcal/mol in the gas phase and 17.12 kcal/mol in the pentanol solvent. Remarkably, these values match closely to the determined experimental values as well as the energy barrier (∼19 kcal/mol) observed in the earlier experimental investigations. , Prior studies have shown that TBD is an effective catalyst for many different types of transesterification processes, including vitrification, ring-opening polymerization, and depolymerization of aromatic esters. , It is also hypothesized that the TBD molecule’s bifunctionality affects the RC development . The nitrogen atom gives electron density as a nucleophile, while the hydrogen atom receives electron density as an electrophilic group.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Indeed, the ultimate energy values obtained from CCSD­(T) calculations stand at 18.56 kcal/mol in the gas phase and 17.12 kcal/mol in the pentanol solvent. Remarkably, these values match closely to the determined experimental values as well as the energy barrier (∼19 kcal/mol) observed in the earlier experimental investigations. , Prior studies have shown that TBD is an effective catalyst for many different types of transesterification processes, including vitrification, ring-opening polymerization, and depolymerization of aromatic esters. , It is also hypothesized that the TBD molecule’s bifunctionality affects the RC development . The nitrogen atom gives electron density as a nucleophile, while the hydrogen atom receives electron density as an electrophilic group.…”
Section: Resultssupporting
confidence: 87%
“…In our previous work, we utilized a two-element Maxwell model to determine the activation energies for the fast and slow modes of 15.7 and 16.6 kcal/mol for Si2-PDAA and 21.9 and 22.9 kcal/mol for Si8-PDAA vitrimer networks . The results are consistent with previously demonstrated siloxane-containing vitrimer networks catalyzed by TBD. , While these values correspond to siloxane exchange and transesterification occurring within the material, determining which activation energy corresponds to which dynamic bond mechanism was not feasible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations